Are interventions to promote healthy eating equally effective for all? Systematic review of socioeconomic inequalities in impact. (December 2015) - McGill, Rory; Anwar, Elspeth; Orton, Lois; Bromley, Helen; Lloyd-Williams, Ffion; O'Flaherty, Martin; Taylor-Robinson, David; Guzman-Castillo, Maria; Gillespie, Duncan; Moreira, Patricia; Allen, Kirk; Hyseni, Lirije; et al.
Abstract Background Interventions to promote healthy eating make a potentially powerful contribution to the primary prevention of non communicable diseases. It is not known whether healthy eating interventions are equally effective among all sections of the population, nor whether they narrow or widen the health gap between rich and poor. We undertook a systematic review of interventions to promote healthy eating to identify whether impacts differ by socioeconomic position (SEP). Methods We searched five bibliographic databases using a pre-piloted search strategy. Retrieved articles were screened independently by two reviewers. Healthier diets were defined as the reduced intake of salt, sugar, trans-fats, saturated fat, total fat, or total calories, or increased consumption of fruit, vegetables and wholegrain. Studies were only included if quantitative results were presented by a measure of SEP. Extracted data were categorised with a modified version of the"4Ps" marketing mix, expanded to6 "Ps": "Price, Place, Product, Prescriptive, Promotion, and Person". Results Our search identified 31, 887 articles. Following screening, 36 studies were included: 18 "Price" interventions, 6 "Place" interventions, 1 "Product" intervention, zero "Prescriptive" interventions, 4 "Promotion" interventions, and 18 "Person" interventions. "Price" interventions were most effective in groups with lower SEP, and may therefore appear likely to reduce inequalities. All interventions that combined taxes and subsidies consistently decreased inequalities. Conversely, interventions categorised as "Person" had a greater impact with increasing SEP, and may therefore appear likely to reduce inequalities. All four dietary counselling interventions appear likely to widen inequalities. We did not find any "Prescriptive" interventions and only one "Product" intervention that presented differential results and had no impact by SEP. More "Place" interventions were identified and none of these interventions were judged as likely to widen inequalities. Conclusions Interventions categorised by a "6 Ps" framework show differential effects on healthy eating outcomes by SEP. "Upstream" interventions categorised as "Price" appeared to decrease inequalities, and "downstream" "Person" interventions, especially dietary counselling seemed to increase inequalities. However the vast majority of studies identified did not explore differential effects by SEP. Interventions aimed at improving population health should be routinely evaluated for differential socioeconomic impact.